The renewability and quality of shallow groundwater in Sanjiang and Songnen Plain, Northeast China - Bing ZHANG; Xian-fang SONG; Ying-hua ZHANG; Dong-mei HAN; Chang-yuan TANG; Lihu YANG; Zhong-liang WANG (Journal of Integrative Agriculture, 2017)
Groundwater is a key component for water resources in Sanjiang and Songnen Plain, an important agriculture basement in China. The quality and the renewability of irrigation groundwater are essential for the stock raising and agricultural production. Shallow groundwater was sampled and analyzed for various variables. The salinity sodium concentration and bicarbonate hazard, were examined with regard to the United States Department of Agriculture (USDA) irrigation water standards. The concentration of chlorofluorocarbons (CFCs) was determined to analyze the age of groundwater. Most groundwater samples labeled as excellent to good for irrigation with low salinity hazard or medium salinity hazard. Four groundwater samples were good and suspected for irrigation with high salinity hazard. Generally groundwater in Sanjiang Plain was younger than the groundwater in Songnen Plain. Meanwhile, groundwater nearby river is younger than the groundwater further away inside the watershed. The mean age of groundwater in Sanjiang Plain is in average of 44.1, 47.9 and 32.8 years by CFC-11 (CCl3F), CFC-12 (CCl2F2) and CFC-113 (C2Cl3F3), respectively. The mean ages of groundwater in Songnen Plain is in average of 46.1, 53.4, and 40.7 years by CFC-11, CFC-12 and CFC-113, respectively. Thus, groundwater nearby rivers could be directly exploited as irrigation water. Partial groundwater has to be processed to lower the salt concentration rather than directly utilized as irrigation water in Songnen Plain. Both water quality and renewability should be put in mind for sustainable agricultural development and water resources management.